Review of Hervé Lacombe. 2001. The Keys to French Opera in the Nineteenth Century. Translated by Edward Schneider. Berkeley: University of California Press - Speare, Mary Jean (Current Musicology, 2002)
Hervé Lacombe’s The Keys to French Opera in the Nineteenth Century, a revised and expanded translation of his Les voies de l’opéra français au XIXe siècle (1997), is a brilliant study that, as the title suggests, provides keys to understanding French opera. Early on, Lacombe argues that nineteenth-century French opera was “governed by a complex set of codes and practices”. He then explores the many elements that make up these conventions by dividing the book into three parts-“Genesis, Performance and Reception,” “Drama, Poetry, and Music,” and “Society, Genre, and Aesthetics” each of which is further divided into three chapters. Lacombe emphasizes the fact that the three parts overlap. While he clearly states his point that artistic and sociological matters intersect, the book’s organization results in some structural choices whereby Lacombe returns to certain topics in a circular fashion.